CONCERNING THE USE OF THE TERMS "VALUES" AND "COSTS" IN UKRAINIAN PHILOSOPHY - Boychenko, Mykhailo (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2023)
The philosophical usage of the terms "value as worth" ("vartosti") and "value as costs" ("tsinnosti") in the Ukrainian language has been studied. It is proved that it needs its fundamental and conceptual philosophical clarification. It was revealed, in particular, that the use of the term "value as costs" ("tsinnosti") is unjustifiably and inappropriately widespread in the Ukrainian everyday and scientific language, while the Ukrainian language also has the term "value as worth" ("vartosti") and its derivatives, which denote the sphere of significance, that is basic to any possible values. It is concluded that the Ukrainian language as a language of philosophy has its own potential, which in relation to the category of "worth" and its subordinate concept of "value as worth" turns out to be richer than the potential of older and most recognized languages of philosophy. It is about distinguishing three types of values: unconditional, conditional and negative values. Conditional values as worth in certain research situations can be called values as costs, at the same time it has been proven that unconditional and negative values cannot be values as costs, therefore it is necessary to rethink the use of the terms "value as worth" ("vartosti’) and "value as costs" ("tsinnosti’) not only in the field of philosophy common to all knowledge, but also in special areas of individual humanitarian, social and other sciences. In each such area, such a rethinking can lead to different contextual terminological solutions, but it is proposed to consistently adhere to the general principle of distinguishing between the terms "value as worth" ("vartosti") and "value as costs" ("tsinnosti").